2021
DOI: 10.1021/acs.analchem.1c00150
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Multi-attribute Analysis of Antibody-Drug Conjugates Enabled by Trapped Ion Mobility Spectrometry and Top-Down Mass Spectrometry

Abstract: Antibody-drug conjugates (ADCs) are one of the fastest growing classes of anticancer therapies. Combining the high targeting specificity of monoclonal antibodies (mAbs) with cytotoxic small molecule drugs, ADCs are complex molecular entities that are intrinsically heterogeneous. Primary sequence variants, varied drug-toantibody ratio (DAR) species, and conformational changes in the starting mAb structure upon drug conjugation must be monitored to ensure the safety and efficacy of ADCs. Herein, we have develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 65 publications
0
43
0
Order By: Relevance
“…However, when operated properlykeeping potentials low and not overfilling -TIMS can be a powerful tool for a broad range of native applications 59,60 . Further opportunities may arise from the combination of ion fragmentation in or before TIMS 61,62 , followed by a MS 3 analysis of the mobility-separated fragment ions with PASEF.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…However, when operated properlykeeping potentials low and not overfilling -TIMS can be a powerful tool for a broad range of native applications 59,60 . Further opportunities may arise from the combination of ion fragmentation in or before TIMS 61,62 , followed by a MS 3 analysis of the mobility-separated fragment ions with PASEF.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Recent work on newer generations of this instrument platform are capable of efficiently transferring higher m/z species and future work investigating their CIU capabilities are needed. 41…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, this is the first study where timsTOF is applied for neuropeptide and sORF discovery and only the second top-down MS study where non-digested peptide samples are identified using a timsTOF. The other study using top-down sample developed a new method for antibody-drug conjugate identification (Larson et al, 2021). To accommodate the fourdimensional data space (4D) of timsTOF data, mass over charge, retention time, intensity and ion mobility, specific modifications were newly implemented to commonly used search engines.…”
Section: Discussionmentioning
confidence: 99%
“…This can only be done when sufficient timsTOF datasets become available in the future. Together with a recent study to identify antibody-based drug products (Larson et al, 2021), this is only the second study where top-down strategies are analyzed on a timsTOF pro mass spectrometer. Alternatively, the spectral intensities could be predicted by a different algorithm, that is reported to be more robust toward different data characteristics, like PROSIT (Gessulat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%